The Effect of ABC Newsradio Australia on Students’ Listening on Third Semester Students of English Department Islamic University of Malang - Mohammad Kurdi Wijaya; Tera Athena (Penerbit STKIP PGRI Bangkalan, 2021)
Listening is one receptive skill which represents students’ ability in understanding a language. Nowadays, media have certain rule to influence this listening skill; e- radio (ABC Newsradio Australia) becomes one effective medium to increase students’ listening skill. This article aims to investigate the effect of e-radio on listening achievement of third semester students of English department at Islamic University of Malang. Pre-experimental research is used as the research design with the pre-test and post-test as the main instrument. The result of T-test showed that there is significant effect of the using e-radio on students’ listening achievement.